2022
DOI: 10.1186/s12904-022-01015-1
|View full text |Cite
|
Sign up to set email alerts
|

Finding their place – general practitioners' experiences with palliative care—a Norwegian qualitative study

Abstract: Background Modern palliative care focuses on enabling patients to spend their remaining time at home, and dying comfortably at home, for those patients who want it. Compared to many European countries, few die at home in Norway. General practitioners’ (GPs’) involvement in palliative care may increase patients’ time at home and achievements of home death. Norwegian GPs are perceived as missing in this work. The aim of this study is to explore GPs’ experiences in palliative care regarding their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Individual PCTs’ propensity to ‘take over’ and provide total care for their patients could not fully explain differences in culture, as GPs from different municipalities affiliated with the same PCT could give contradictory descriptions of how the PCT team acted. The different cultures seemed to follow a pattern consistent with previous findings showing that rural GPs are more involved in palliative care than their urban colleagues [ 26 , 27 , 39 ]. Although this could mean that rural residents benefit from the close involvement of GPs, the finding must also be seen in light of the fact that the demands for specialised palliative care services in Norway exceed the existing resources [ 3 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Individual PCTs’ propensity to ‘take over’ and provide total care for their patients could not fully explain differences in culture, as GPs from different municipalities affiliated with the same PCT could give contradictory descriptions of how the PCT team acted. The different cultures seemed to follow a pattern consistent with previous findings showing that rural GPs are more involved in palliative care than their urban colleagues [ 26 , 27 , 39 ]. Although this could mean that rural residents benefit from the close involvement of GPs, the finding must also be seen in light of the fact that the demands for specialised palliative care services in Norway exceed the existing resources [ 3 ].…”
Section: Discussionsupporting
confidence: 85%
“…GPs’ experiences with palliative care, including reflections about their role, were explored. They were thereafter presented with extracts from the guideline, and the descriptions of their role and competence requirements were discussed [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It has been consistently reported that patients prefer to have palliative conversations in the primary care setting as their relationships with their FPs allow for more individualized and effective dialogue. 21,23,24…”
Section: Discussionmentioning
confidence: 99%
“…22 It has been consistently reported that patients prefer to have palliative conversations in the primary care setting as their relationships with their FPs allow for more individualized and effective dialogue. 21,23,24 The current literature also identified ongoing barriers to FPs engaging in palliative conversations. These included physician-dependent uptake (often related to comfort and experience), demands on time, lack of compensation/value for the work, and limited practical resources.…”
Section: Alignment With Existing Literaturementioning
confidence: 99%